(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Regular physical activity (PA) is crucial for maintaining overall health and preventing chronic diseases. Nursing students, as future healthcare professionals, are expected to adopt and promote healthy behaviors. Objective: This study aimed to assess the knowledge, attitude, and practice (KAP) levels toward physical activity among nursing students at the College of Nursing, Rawalpindi. Methods: A cross-sectional study was conducted using an online self-administered questionnaire. A universal sampling technique targeted all 490 students, with 388 responses received. Data were analyzed using SPSS version 26.0. Descriptive analysis assessed KAP levels. Spearman’s rank correlation test examined relationships between KAP components, while Chi-square and Fisher’s Exact tests determined associations with demographic variables. A significance level of p < 0.05 was considered statistically significant. Results: The findings showed that 97.7% of participants had high knowledge, and 96.9% had a positive attitude toward physical activity. However, only 42% engaged in satisfactory physical activity practices, while 58% exhibited unsatisfactory practices. Correlation analysis indicated a significant positive relationship between knowledge and attitude (r = 0.170, p = 0.001) but no significant correlation between knowledge and practice (r = -0.077, p = 0.130). Surprisingly, a significant negative correlation was found between attitude and practice (r = -0.150, p = 0.003). Designation (p = 0.000) and BMI (p = 0.001) were significantly associated with physical activity practices, with overweight participants showing better engagement. Conclusions: Despite high knowledge and positive attitudes, physical activity practices among nursing students remain inadequate. The study highlights the need for targeted interventions, such as structured exercise programs and awareness campaigns, to bridge the gap between knowledge and action. Institutional support and policy changes could encourage students to incorporate physical activity into their daily routines.